The Strategic Plan for the forest restoration in humid terrestrial ecosystems in the Guayas province (Ecuador) (Revista Científica Ciencias Naturales y Ambientales, 2017)
The main ecosystems of the province of Guayas have undergone processes of conversion of land use, reaching in cases to high levels of degradation due to deforestation, since there are isolated restoration initiatives, as well as a scarce articulation between public and / or private institutions, with little community participation, this study developed a proposal for the forest restoration of humid ecosystems, which was developed through a diagnosis of the current situation, interviews with specialists in botany, planning and restoration, to develop criteria on the mission, vision, strategic objectives, operational objectives, actions, minimum goals and species suggested for propagation. Additionally, a preliminary prioritization of the potential areas for forest restoration was developed for localities in Guayas that possess this type of ecosystem.
Keywords: humid ecosystems; strategic planning; active restoration; passive restoration